2010
DOI: 10.1002/dc.21464
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasonography‐guided fine‐needle aspiration for diagnosing upper gastrointestinal submucosal lesions: A prospective study of 50 cases

Abstract: The objective was to assess EUS-FNA for diagnosing intramural upper GI tract lesions. The subjects were 50 patients (21M/29F) with upper GI submucosal lesions who underwent EUS-FNA at a referral center for GI system over a 12-month period. All cases were followed for 1 year after initial EUS-FNA. Cytologic diagnoses were categorized as benign, malignant, suspicious for malignancy, mesenchymal tumor, endocrine tumor, or nondiagnostic. All tumors were assessed for various cytomorphologic features. The accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…Turhan et al19 performed a prospective study of EUS-FNA for diagnosis of upper gastrointestinal submucosal lesions and reported 82.9%, 73.3%, 87.9%, 64.7%, and 80% for the sensitivity, specificity, positive, and negative predictive values and accuracy of EUS-FNA, respectively, for upper gastrointestinal tract submucosal mesenchymal tumors.…”
Section: Diagnostic Yield Of Eus-fna In Smtsmentioning
confidence: 99%
“…Turhan et al19 performed a prospective study of EUS-FNA for diagnosis of upper gastrointestinal submucosal lesions and reported 82.9%, 73.3%, 87.9%, 64.7%, and 80% for the sensitivity, specificity, positive, and negative predictive values and accuracy of EUS-FNA, respectively, for upper gastrointestinal tract submucosal mesenchymal tumors.…”
Section: Diagnostic Yield Of Eus-fna In Smtsmentioning
confidence: 99%
“…In a prospective study by Turhan et al, the sensitivity, specificity, positive and negative predictive values, and accuracy of EUS-FNA for diagnosing submucosal mesenchymal tumors of upper GI tract were 82.9%, 73.3%, 87.9%, 64.7%, and 80%, respectively. The corresponding values for nonmesenchymal lesions were 100%, 85.7%, 80%, 100%, and 90.9% [13]. …”
Section: Discussionmentioning
confidence: 99%
“…EUS-FNA has become a staple in the evaluation of GISTs67 owing to the generally low risk of related complications, such as hemorrhage, bacteremia, pneumoperitoneum, bacterial peritonitis, and perforation 89. However, serious consequences may be resulted in whenever these tumors are breached.…”
Section: Discussionmentioning
confidence: 99%